A comparison study of periapical repair in dogs' teeth using RoekoSeal and AH plus root canal sealers: A histopathological evaluation - Leonardo, Mario Roberto; Herzog Flores, Daniel Silva; Garcia de Paula e Silva, Francisco Wanderley; Leonardo, Renato de Toledo [UNESP]; Bezerra da Silva, Lea Assed (Elsevier B.V., 2008)
The objective of the study was to evaluate the biocompatibility of RoekoSeal sealer Roeko (Dental Products, Langenau, Germany) with the periapical tissues of dogs and compare it with AH Plus sealer (Dentsply/De Trey, Konstanz, Germany). The pulps of 32 root canals were removed, the apical cementum layer perforated, the biomechanical preparation performed, and the root canals filled by lateral condensation technique. Ninety days after the surgery, the animals were euthanized, the bone with teeth removed, and the samples prepared for histopathological analysis. In group 1 (RoekoSeal Automix), deposition of mineralized tissue was observed, with complete newly mineralized apical formed tissue in 43.8% and partial sealing in 56.2%. In group 2 (AH Plus), in 12.5% there was complete newly mineralized apical formed tissue, in 75% the sealing was partial, and in 12.5% there was no sealing (p < 0.05). There were no differences between the groups in relation to the inflammatory infiltrate; thickness of the periodontal ligament; and the resorption of dentin, cementum or bone (p > 0.05).
Keywords: AH plus; biocompatibility; endodontic sealer; RoekoSeal